Extended plasma half-life of albumin-binding domain fused human IgA upon pH-dependent albumin engagement of human FcRn in vitro and in vivo - Simone Mester; Mitchell Evers; Saskia Meyer; Jeannette Nilsen; Victor Greiff; Inger Sandlie; Jeanette Leusen; Jan Terje Andersen (Taylor & Francis Group, 2021)
Albumin has a serum half-life of 3 weeks in humans. This feature can be used to improve the pharmacokinetics of shorter-lived biologics. For instance, an albumin-binding domain (ABD) can be used to recruit albumin. A prerequisite for such design is that the ABD-albumin interaction does not interfere with pH-dependent binding of albumin to the human neonatal Fc receptor (FcRn), as FcRn acts as the principal regulator of the half-life of albumin. Thus, there is a need to know how ABDs act in the context of fusion partners and human FcRn. Here, we studied the binding and transport properties of human immunoglobulin A1 (IgA1), fused to a Streptococcus protein G-derived engineered ABD, in in vitro and in vivo systems harboring human FcRn. IgA has great potential as a therapeutic protein, but its short half-life is a major drawback. We demonstrate that ABD-fused IgA1 binds human FcRn pH-dependently and is rescued from cellular degradation in a receptor-specific manner in the presence of albumin. This occurs when ABD is fused to either the light or the heavy chain. In human FcRn transgenic mice, IgA1-ABD in complex with human albumin, gave 4-6-fold extended half-life compared to unmodified IgA1, where the light chain fusion showed the longest half-life. When the heavy chain-fused protein was pre-incubated with an engineered human albumin with improved FcRn binding, cellular rescue and half-life was further enhanced. Our study reveals how an ABD, which does not interfere with albumin binding to human FcRn, may be used to extend the half-life of IgA.Abbreviations: ABD - Albumin binding domain, ADA - anti-drug-antibodies, ADCC - Antibody-dependent cellular cytotoxicity, ELISA - Enzyme-linked Immunosorbent assay, FcαRI - Fcα receptor, FcγR - Fcγ receptor, FcRn - The neonatal Fc receptor, GST - Glutathione S-transferase, HC - Heavy chain, HERA - Human endothelial cell-based recycling assay, Her2 - Human epidermal growth factor 2, HMEC - Human microvascular endothelial cells, IgG - Immunoglobulin G, IgA - Immunoglobulin A, LC - Light chain, QMP - E505Q/T527M/K573P, WT - Wild type